Analysis of students’ social studies learning experiences using the video-assisted make a match model at SMP Kristen Shining Stars - Melisa Br Tarigan; I Nengah Suastika; Luh Indrayani; Ketut Sedana Arta (ARKA INSTITUTE, 2025)
This study aims to explore junior high school students’ learning experiences in Social Studies (IPS) through the Make a Match learning model assisted by video media. Employing a qualitative phenomenological approach, data were collected through observations, in-depth interviews, and participatory documentation. The research was conducted at SMP Kristen Shining Stars, Mimika Regency, Central Papua, with eighth-grade students as participants. The analysis of data revealed three dominant conditions in the implementation of the Make a Match model assisted by video: increased learning activity, enjoyable learning and stronger social engagement, and more meaningful learning experiences. The findings indicate that video-assisted learning helped students connect theoretical concepts of Social Studies with real-life contexts, thereby enhancing understanding and retention. The Make a Match activity also fostered motivation, collaboration, and enjoyment, transforming the learning process from memorization into an interactive experience of constructing social meaning.